KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK - Riftandi, Deni; Suking, Arifin; Ardhian, Nur Luthfi (Equity In Education Journal, 2024)
This study aims to describe the leadership role of the principal in implementing the driving school program at SMAN 6 Gorontalo, in terms of his role as: (1) leader of learning transformation, (2) facilitator, (3) communicator, and (4) implementer of monitoring and evaluation. This research uses a qualitative approach with a case study design. The data collection techniques used were interviews, observation and documentation. The data analysis technique used interactive data analysis, supported by checking the validity of the data using triangulation techniques. The results of this study show: (1) the principal as the leader of learning transformation, has succeeded in improving the quality of learning well through the implementation of the Mobile School Program, (2) the principal as a facilitator has actively facilitated the implementation of the Mobile School Program through various innovative initiatives, (3) the principal as a communicator has succeeded in uniting all school components to actively participate in the implementation of the Mobile School program, and (4) the principal as the implementer of the mobile school program conducts active monitoring and evaluation based on the predetermined success indicators.